Coexistence of mixed phenotype Creutzfeldt‐Jakob disease, Lewy body disease and argyrophilic grain disease plus histological features of possible Alzheimer's disease: A multi‐protein disorder in an autopsy case. Issue 1 (3rd September 2014) - Fernández‐Vega, Iván; Ruiz‐Ojeda, Javier; Juste, Ramon A.; Geijo, Maria; Zarranz, Juan Jose; Sánchez Menoyo, Jose Luis; Vicente‐Etxenausia, Ikerne; Mediavilla‐García, Jennifer; Guerra‐Merino, Isabel
<x xml:space="preserve">Abstract</x> We report hereby an autopsy case of sporadic mixed phenotype CJD without hereditary burden and a long‐term clinical course. An 80‐year old man was diagnosed with mild cognitive impairment 27 months before death, caused by bronchopneumonia and severe respiratory impairment. During this time, the patient developed gradual mental deterioration, some sleeping problems and myoclonus. Other clinical manifestations were progressive gait problems, language deterioration, presence of primitive reflexes and irritability. In keeping with those symptoms, a rapidly evolving dementia was clinically suspected. Cerebrospinal fluid test for 14‐3‐3 protein was negative. However, an abnormal EEG and MRI at end‐stage of disease were finally consistent with CJD. Post‐mortem examination revealed a massive cortical neuronal loss with associated reactive astrocytosis, also evident in the white matter. Diffuse spongiform changes involving some basal ganglia, especially medial thalamus, some troncoencephalic nuclei, mainly inferior olivary nucleus and the molecular layer of the cerebellum were seen. Immunorreactive deposits for anti‐prion protein antibody were present at different areas of the CNS. Additionally, Lewy bodies were observed at the brainstem and amygdala. Furthermore, argirophilic grains together with oligodendroglial coiled bodies and pre‐tangle inclusions in the neurons from the limbic system containing hyperphosphorylated 4R tau were noted. To the best of our knowledge, this is the first case of CJD combined with Lewy body disease and argirophilic grain disease. Furthermore, we believe this case is an extremely rare combination of MM2‐cortical‐type and MM2‐thalamic‐type sporadic CJD (sCJD), which explains the broad spectrum of MM2‐type sCJD findings and symptoms. Moreover, histological features of possible Alzheimer's disease were also reported.